Formulation and physicochemical and sensory characterization of an Andean Carchense flavored semi-mature cheese - Manríquez Rojas, María José; Paredes Pita, Carlos Arturo; Torres Mayanquer, Freddy Giovanny (SATHIRI, 2022)
The present Project was aimed to formulate and characterize a type of semi-ripe flavored Andean from Carchi – Ecuador, using Pizán milk as raw material. It was carried out an experiment in triplicate under a completely randomized design in two phases. The first one referring to the contextualization of the cheese evaluating raw material coming from two cattle breeds, type of microorganisms and final temperature of the cheese draining. The best treatment was obtained through a sensory analysis, corresponding to a cheese made with Pizán milk from, L. delbrueckii and L. helveticus lactic culture, draining temperature of 44°C, and matured for 28 days. This treatment was base to elaborate the second phase in which the addition of sauces and the coating to the crust were evaluated. In this case, the major acceptability was presented with the treatment flavored with pesto, matured for 28 days and with a coating of dehydrated species. The three best treatments were subjected to a fat, protein and humidity analysis resulting in 39%, 10.5% and 51% respectively. Such percentages are within the range established in the NTE INEN 2607. The microbiological analysis determined the absence of Enterobacteriaceae and Staphyloccocus aureus which implicate that the product is completely innocuous. Based on these statements, it can be concluded that the Pizán milk complies with the physicochemical parameters required to the production of ripened semi-hard cheeses, the milk of this breed is rich in macronutrients.